EVALUATION OF HEAVY METALS AROUND THE MINING OF DECORATIVE STONE ORE IN SUSONG COUNTY LIAOHE RIVER (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
In order to study the pollution of heavy metals around Liaohe Fender stone mine in Susong County, the soils at six points and the sediment at four points were selected. The effects of heavy metals Cu, Zn, Pb, Cd, Cr , Ni ,Hg and As were measured, the single factor index and the Nemero index method were used to evaluate the heavy metal elements in soil and sediment. The results showed that the values of heavy metal elements in the soil and sediment were less than 1 and the Pintegrated values were less than 0.85,the mine area was not polluted by heavy metals and belonged to the clean area within the grade Ⅰ.